Unattainable equipoise in randomised controlled trials: staff views of a feasibility study of surgical treatments for segmental tibial fractures - Phelps, EE; Tutton, E; Costa, ML; Hing, CB; STIFF-F research collaborators (British Editorial Society of Bone and Joint Surgery, 2021)
Aims: To explore staff’s experience of a multi-centre pilot randomised controlled trial (RCT) comparing intramedullary nails and circular frame external fixation for segmental tibial fractures.